Человек боя: роман / В. В. Головачев - Головачев Василий Васильевич (Абсолютное оружие, 2001)
Экземпляры: Ф-22 (20200710) / Инвентарный номер: 95606 / Цена: / Сис.шифр: 84(2=411.2))6-4 / Авт.знак: Г 61 / ББК: 84(2=411.2))6-4